Pellucidar - Burroughs, Edgar Rice, 1875-1950 (Salt Lake City, UT : Project Gutenberg, 1996)
"Pellucidar" by Edgar Rice Burroughs is a fantasy novel written during the early 20th century. The story revolves around David Innes, who embarks on a journey to the inner world of Pellucidar, a strange realm that exists at the core of the Earth, where time and societal norms differ greatly from the outer world. This fantastical setting features prehistoric creatures and primitive tribes, and serves as a backdrop for adventures filled with danger, intrigue, and the relentless struggle between different races. The opening of "Pellucidar" sets the stage for an exciting expedition following a letter that piques David's curiosity regarding the mysterious inner world. After experiencing a strange discovery in the Sahara desert, David feels compelled to revisit Pellucidar, which he had previously explored. As he prepares for his journey, he reflects on his past adventures and the friends he left behind, including Dian the Beautiful, hinting at the emotional stakes involved. The first chapter introduces the labyrinthine landscapes of Pellucidar and the challenges David faces as he navigates through an unfamiliar environment filled with both threats and wonders. The stage is set for an epic quest fueled by love and friendship, as he searches for his beloved Dian amidst the primal chaos of this unique world. (This is an automatically generated summary.)
Release date is 1996-07-01
Judith Boss
Keywords: Science fiction; Adventure stories; Earth (Planet) -- Core -- Fiction